Acute hearing loss in patients with hematological disorders. (July 2015) - Lin, Chien-Ta; Chiang, Ching-Wen; Young, Yi-Ho
Abstract Objective: This study adopted an inner ear test battery to investigate the causes of acute sensorineural hearing loss in patients with hematological disorders. Methods: During the past 20 years, the authors have experienced 14 patients with hematological disorders, i.e. leukemia or aplastic anemia, having acute sensorineural hearing loss. An inner ear test battery comprising audiometry and cervical vestibular-evoked myogenic potential (cVEMP), ocular VEMP (oVEMP), and caloric tests was performed. Results: Diagnoses comprised of sudden sensorineural hearing loss in 12 patients and endolymphatic hydrops in four patients (two patients had one ear with sudden sensorineural hearing loss while the other ear had endolymphatic hydrops). Percentages of recruitment phenomenon showed a significant difference between endolymphatic hydrops and sudden sensorineural hearing loss. Abnormal percentages for mean hearing level (86%), cVEMP test (71%), oVEMP test (25%), and caloric test (14%) exhibited a significant sequential decline in these patients. Conclusion: Acute sensorineural hearing loss in a patient with leukemia or aplastic anemia may be related to either sudden sensorineural hearing loss or endolymphatic hydrops. A significant sequential decline in the function of the cochlea, saccule, utricle, and semicircular canals indicates that the pars inferior is more vulnerable to blood insult than the pars superior.